OPTIMIZATION IN IMPLEMENTATION OF PUBLIC SERVICE INFORMATION SYSTEM IN SOUTH BANJARMASIN DISTRICT, SOUTH KALIMANTAN - Riska Aulia Noor; Rizky Subhan; Fika Fibriyanita; Beni Akhmad (RADJA PUBLIKA, 2025)
The importance of public service information systems is currently a high level of need. This is based on the consideration that the population growth in Indonesia is very rapid, the level of needs and the growing economy, as well as the effectiveness and efficiency of handling public services. The public service information system in question is a service system based on information technology, where the availability of applications and capable systems facilitates the achievement of providing optimal services to the community, as well as learning for the community so that they can realize the importance of personal documents so that the fulfillment of service needs can be carried out easily and quickly. The components of this public service information system include service applications, authorized government official structures, competent government employees, and clear service procedures. This can be realized along with the level of need for efficiency in the implementation of task performance and service delivery from government employees to the public.